Reliability and Validity of a Weight-Bearing Measure of Ankle Dorsiflexion Range of Motion - Chisholm, Martin D. (University of Toronto Press Incorporated, 2012)
Purpose: To examine reliability and validity of the Lunge Test (LT) of dorsiflexion range of motion and determine the impact of different approaches to obtain a score on these parameters. Methods: Fifty-three patients with ankle injury/dysfunction provided initial assessment data for cross-sectional convergent and known-groups validity analysis with the Pearson coefficient (r) and paired t-test, respectively; data after 4–8 weeks of treatment for longitudinal validity analysis with coefficient r; and data 3 days later for test–retest reliability using the intra-class correlation coefficient (ICC) and minimal detectable change (MDC). LT scores were determined for the affected leg only (LT(Aff)) and for the difference between the two limbs (LT(Diff)). Two strategies were used to calculate LT scores: a single series and the mean of three series of lunges. LTs were correlated with the Lower Extremity Functional Scale and Global Foot and Ankle Scale. Results: Reliability coefficients were high (ICC=0.93–0.99). The MDC=1.0/1.5 cm, LT(Aff)/LT(Diff), respectively. Cross-sectional validity was confirmed for LT(Diff) (r=−0.40 to −0.50). Between-limb differences (p<0.05) supported known-groups validity. Longitudinal validity was supported for both LT change scores (r=0.39–0.63). The number of series of lunges used did not impact results. Conclusions: A single series of lunges produces a reliable LT score. From a validity perspective, clinicians should use LT(Diff) on initial assessment and either LT to assess change.